The Effectiveness of Collaborative Academic Online Based Learning through Students’ Self-Regulated Learning - Erfan Priyambodo (Intelektual Pustaka Media Utama, 2016)
Nowdays, learning through e-learning is going rapidly, including the application BeSmart UNY. This application is providing collaborative method in teaching and learning. The aim of this study was to determine the effectiveness of the Collaborative Academic Online Based Learning method in teaching and learning toward students’ Self-Regulated Learning (SRL) on Vocational School Chemistry courses. This study was quasi-experimental research method with one group pretest posttest design. Instruments used in this study were lesson plan and questionnaire of students’ SRL. This questionnaire is filled by students through BeSmart UNY. In determining the differences SRL before and after teaching and learning processes, the data was analized by stastitical method. The results showed that the implementation of the Collaborative Academic Online Based Learning method in teaching and learning was effective for improving students’ SRL.